Storage of Data in DNA - Haque, Anwar Ul (International Journal of Pathology, 2023)
Ours is super communication age. All over the world enormous amount of data is being generated every second from every phone, every computer, every device in every office, home, school, college, university, hospital, shop, industry, institution and moving vehicle etc. This gigantic and titanic volume of information has almost depleted our data storing capacity on internet. Scientists are therefore trying very hard to find out alternate and more spacious capacity.